The Dilemma of Misclassification Rates in Senior Patients With Prostate Cancer, Who Were Treated With Robot-Assisted Radical Prostatectomy: Implications for Patient Counseling and Diagnostics - Liakos, Nikolaos; Witt, Joern H.; Rachubinski, Pawel; Leyh-Bannurah, Sami-Ramzi (Frontiers in Surgery, 2022)
ABSTRACT: Objectives: There is a recent paradigm shift to extend robot-assisted radical prostatectomy (RARP) to very senior prostate cancer (PCa) patients based on biological fitness, comorbidities and clinical PCa assessment that approximates true risk of progression. Thus, we aimed to assess misclassification rates between clinical vs. pathological PCa burden. Materials and Methods: We compared senior PCa patients ≥ 75 yrs. (n=847), who were propensity score matched with younger patients <75. yrs. (n=3388) in a 1:4 ratio. Matching was based on number of biopsy cores, prostate volume and preoperative Cancer of the Prostate Risk Assessment (CAPRA) risk groups score. Multivariable logistic regression models (LRM) predicted CAPRA-S upgrade, which was defined as higher-risk of the surgical CAPRA (CAPRA-S) in presence of lower-risk preoperative CAPRA score. LRM incorporated same variables as propensity score matching. Moreover, patients were categorized as low-, intermediate- and high-risk, preoperative and according to their CAPRA and CAPRA-S score. Results: CAPRA-S risk strata significantly differed between the groups. Greater proportions of unfavorable intermediate risk (39% vs. 32%) or high risk (30 vs. 28%; p<0.001) were observed. These proportions are driven by greater proportions of ISUP Gleason Grade Group 4 or 5 (33 vs. 26%; p=0.001) and pathological tumor stage (≥T3a 54% vs. 45%; p<0.001). Increasing age was identified as independent predictor of CAPRA-S based upgrade (age OR 1.028 95% CI 1.02-1.037; p<0.001) Conclusion: Approximately every second senior patient has a misclassification in (i.e. any up- or downgrade) and each 4.5th senior patient specifically has an upgrade in his final pathology that directly translates to unfavourable PCa prognosis. It is imperative to take such substantial misclassification rates into account for this sensitive PCa demographic of senior men. Future prospective studies are warranted to further optimize PCa workflow and diagnostics, such as incorporating modern imaging, molecular profiling and implement these into biopsy strategies to identify true PCa burden.